The Role of Green Trust as an Intervening Variable in the Relationship Between Green Brand Image and Green Perceived Value Towards Purchase Intention in Indonesian Local Fashion Products - Wahyoedi, Soegeng; Wardhana, Aditya; Tannady, Hendy (CV. Rayyan Dwi Bharata, 2022)
The issue of environmental damage caused by fashion industry continues to increasing every year accompanied by real conditions that accur, either damage on humans, animals, plants, and the environment. Nowadays people are increasingly aware of the importance of preserving the environment more selectively in the selection of products used. This resesrch was conducted to determine the effect of Green Perceived Value and Green Brand Image on Green Purchase Intentionwith Green Trust as an Intervening variable in the case study on fashion product Sejauh Mata Memandang. The number of samples study werw 170 respondent from consumers Sejauh Mata Memandang and also green consumerism. The technique used in this research is purposive sampling. In this study, it shows that the Green Perceived Value and Green Brand Image variables have a significant effect on Green Trust and also Green Purchase Intention. Green Trust does not have a greater influence on each independent variable and also the dependent variable.